VILLAGE GOVERNMENT STRATEGY IN DEVELOPING BUMDES SUMBER LESTARI TOURISM SUMBER DHUWUR WONOSARI VILLAGE - Saputro, Ardian Ahmad; Sukmana, Hendra (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the strategy of the Wonosari Village government in developing BUMDes Sumber Lestari as the manager of Sumber Dhuwur tourism. Method: A descriptive qualitative approach was used to collect data through observation, interviews, and documentation. The research informants were village officials, treasurers, and heads of BUMDes. Results: The results demonstrate that the village government is implementing promotional strategies through social media, collaboration with content creators, and the development of tourism-supporting infrastructure. However, challenges include insufficient funding, suboptimal social media management, and inadequate road infrastructure. Novelty: A SWOT analysis shows that the strengths of Sumber Dhuwur tourism lie in its natural potential and community support, while threats include competition with other destinations and declining visitor numbers. This study found that the SO (Strength-Opportunity) strategy is the primary approach to developing tourism based on local potential. The novelty of this study lies in the use of SWOT analysis in the context of developing a village-owned enterprise (BUMDes) tourism business based on community participation and comprehensive local innovation. These results are expected to serve as a strategic reference in developing sustainable village tourism.